2015
DOI: 10.1002/anie.201502971
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Method for the Synthesis of Long DNA Sequences with Multiple Repeat Units

Abstract: Apolymerase chain reaction (PCR) derived method for preparing long DNA, consisting of multiple repeat units of one to ten base pairs,i sd escribed. Tw os eeding oligodeoxynucleotides,so-called oligoseeds,whichencode the repeat unit and produce ad uplex with 5'-overhangs,a re extended using athermostable archaeal DNApolymerase.Multiple rounds of heat-cool extension cycles,a kin to PCR, rapidly elongate the oligoseed. Tw enty cycles produced long DNAwith uniformly repeating sequences to over 20 kilobases (kb) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The gel-electrophoresis dataf rom both extension reactions, ( Figure S2) indicated that the final DNA products consisted of ar ange of lengths, from 200 bp to 5000 bp, as expected from our previous report on this method using unmodified NTPs. [37] Further analysis of the gel band intensities, (Figure 2A-E, and Figure S7) indicated that in most cases there is minimal differ- Figure 2D. This suggests that, the size and electronegativity of bromine may have steric and/or electronic impacts on the polymerase and the higherc harged ensity and bulk of several neighbouring bromo-modifications might affect the polymerase reading and/or writing processes.O therwise we found little difference in the enzymatic processivity of different types of base modification within the same oligoseed, namely between;i )a single atom or al ong alkyl chain modification on the same base, Figure 2A,B, (cf.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…The gel-electrophoresis dataf rom both extension reactions, ( Figure S2) indicated that the final DNA products consisted of ar ange of lengths, from 200 bp to 5000 bp, as expected from our previous report on this method using unmodified NTPs. [37] Further analysis of the gel band intensities, (Figure 2A-E, and Figure S7) indicated that in most cases there is minimal differ- Figure 2D. This suggests that, the size and electronegativity of bromine may have steric and/or electronic impacts on the polymerase and the higherc harged ensity and bulk of several neighbouring bromo-modifications might affect the polymerase reading and/or writing processes.O therwise we found little difference in the enzymatic processivity of different types of base modification within the same oligoseed, namely between;i )a single atom or al ong alkyl chain modification on the same base, Figure 2A,B, (cf.…”
Section: Resultsmentioning
confidence: 92%
“…The DNA products contain the modified cytidine at every fifth site on just one strand of the extended duplexa nd, in both cases the DNA produced is similar in length to the control reactionu sing the unmodified dCTP. [37] Nucleotides with more sterically demandingm odifications, 6-S-dGTP and 5acetyl-Hg-dCTP,w ere also incorporated into just one strand of the extending DNA but gave shorter products of around 500 bp which could not be further extended with additional cycling ( Figure S2 Ea nd Figure S3). Employing the same starting oligoseed but inserting either am odifiedd ATPo rd TTP results in DNA bearing 4c onsecutive modifications on the same strand.A fter 10 cycles, the methody ields DNA products bearing 7-deaza-7-I-dA (500 bp) and 5-Br-dU (5 kb) ( Figure S2 Ca nd S2 D) and furtherc ycling allows attainment of lengths of modified DNA comparable to that obtained with the native nucleotides.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations